2022
DOI: 10.1111/jfpp.16808
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of DPP‐IV inhibitory potentials of polyphenols existed in Qingke barley fresh noodles: In vitro and in silico analyses

Abstract: The inhibitory effects of 14 phenolic compounds that existed in Qingke barley fresh noodles on dipeptidyl peptidase-IV (DPP-IV) and structure-activity relationship (SAR) was evaluated by in vitro enzyme activity inhibition assay, molecular docking, and molecular dynamics methods. The results showed that the IC 50 and binding affinity of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Additionally, the lowest number of interactions depicted by few numbers of conventional H and van der Waal bonds for the Diprotin A–DPP-IV complex might be suggested as the reason for its lower binding energy score compared to chlorogenic acid–DPP-IV with higher binding energy characterised by a greater number of convention H-bond and van der Waal forces. The higher number of interactions and H-bonds witnessed in this study by chlorogenic acid over Diprotin A was in line with similar work by Tuersuntuoheti et al [ 37 ] where chlorogenic acid isolated from Qingke barley fresh noodles had 19 interactions (nine H-bonds and 10 hydrophobic interactions with amino acids residues of DPP-IV) compared with the used standard (sitagliptin) having 15 interactions (one H-bond and 14 hydrophobic interactions). During the 100 ns simulation period, the conserved residue Tyr510 in the interaction plots of Diprotin A and chlorogenic acid with DPP-IV in each of the time frames studied is relevant to the affinity and stability observed with the two compounds towards the target ( Figure 2 A,C).…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the lowest number of interactions depicted by few numbers of conventional H and van der Waal bonds for the Diprotin A–DPP-IV complex might be suggested as the reason for its lower binding energy score compared to chlorogenic acid–DPP-IV with higher binding energy characterised by a greater number of convention H-bond and van der Waal forces. The higher number of interactions and H-bonds witnessed in this study by chlorogenic acid over Diprotin A was in line with similar work by Tuersuntuoheti et al [ 37 ] where chlorogenic acid isolated from Qingke barley fresh noodles had 19 interactions (nine H-bonds and 10 hydrophobic interactions with amino acids residues of DPP-IV) compared with the used standard (sitagliptin) having 15 interactions (one H-bond and 14 hydrophobic interactions). During the 100 ns simulation period, the conserved residue Tyr510 in the interaction plots of Diprotin A and chlorogenic acid with DPP-IV in each of the time frames studied is relevant to the affinity and stability observed with the two compounds towards the target ( Figure 2 A,C).…”
Section: Resultssupporting
confidence: 92%
“…The inuence of glycosylation depends on the avonoid skeleton and the point of attachment of the sugar unit. Hence, apigenin (29), luteolin (39), and myricetin (65) show better inhibitory effects than their glycosides, while the inhibitory activities of isorhamnetin (53) and kaempferol (56) and were smaller than the corresponding glycosides. Proença et al 39 reported similar results; they based their conclusion on evaluating 140 avonoids (natural and synthetic) using in vitro and ex vivo models.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
“…The most relevant aspects of this study are briey discussed in the next paragraph. Cyanidin 3-O-b-D-glucopyranoside (1), isoliquiritigenin (16), narcissoside (55), myricetin (65), and hyperoside (70) inhibited the enzyme higher than 50% at 200 mM. The IC 50 values of these avonoids were 81.05, 149.96, 166.52, 156.29, and 138.79 mM, respectively.…”
Section: Natural Products With Dpp-iv Inhibitory Propertiesmentioning
confidence: 99%
See 2 more Smart Citations